A comparative study on the ecological footprint of living consumption in northwest ethnic regions: 1980–2018 - Wu, Shifeng; Wang, Jiangyun; Jia, Yinuo; Wang, Xuyan (Frontiers in Environmental Science, 2023)
This paper focuses on the northwest region, which is related to China's overall ecological security and ethnic stability. This paper selects the neighboring regions of Dingxi City, Gannan Tibetan Autonomous Prefecture and Linxia Hui Autonomous Prefecture as the starting point, deeply and systematically analyzes the impact of different lifestyles on the environment. Using environmental economics, ecological economics, environmental sociology and other related theories, ecological footprint were used to investigate different lifestyles’ impact to environment. Neural network were also used to carry out multi-perspective environmental impact research from the spatial scale and time scale. The research finds that Dingxi, Gannan and Linxia’s different mode of production has led to different lifestyle, and results in different impact on environment. The governments of the three places should take actions to promote ecological civilization and encourage the establishment of an ecologically-friendly and environmentally-friendly way of life so as to reduce the impact on the ecological environment and realize regional sustainable development.